High field magnetoresistance of strongly coupled InAs/GaSb superlattices - Deacon, R; Henriques, AB; Nicholas, R; Shields, P (2005)
We investigate vertical magnetotransport measurements in strongly coupled InAs/GaSb superlattices within the miniband transport regime. Sample magnetoresistance curves display oscillations due to the successive un-nesting of Landau level minibands. This qualitative picture is strongly supported by Monte Carlo simulations, which include acoustic and optic phonon scattering as well as Umklapp processes, providing a semi-classical description of the miniband transport.